Design of Batik Crafts Industrial Performance Measurement Model in Wukirsari Region Bantul - Zabidi, Yasrin (Sekolah Tinggi Teknologi Adisutjipto, 2018)
One important factor in influencing the progress and decline of an industry is the performance factor. Performance issues are not only important for middle-to-upper-level companies and large companies, but also important for small and medium industries such as the batik craft industry in the Wukirsari region, Bantul. Given the importance of performance, researchers tried to design a performance measurement model of the batik craft industry in the Wukirsari region, Bantul with the aim of identifying performance criteria, determining performance indicators, formulating performance indicators, and making performance measurement instruments. The steps in this study are divided into four phases, namely the initial research phase and problem formulation, the design phase, the analysis phase and the conclusion phase. The initial research phase and problem formulation include, the profile of the batik craft industry in the Wukirsari region, Bantul, the current performance evaluation system, problem formulation and research objectives. The design phase includes the design process of the performance measurement model with the Balanced Scorecard method which includes setting strategic objectives, establishing performance indicators (key performance indicators), determining performance indicator formulas, making performance measurement instruments. Analysis phase includes KPI analysis and strategy map analysis. Conclusion phase includes conclusions from the results of research and suggestions for the batik craft industry in Wukirsari, Bantul. From the results of the study obtained four performance perspectives based on the balanced scorecard, namely financial, customer, internal business processes, learning and growth. five, namely: increased sales growth, high customer satisfaction, improved system and better work processes, the creation of a good work climate, and increased employee productivity.There are seven performance indicators formed, namely: the rate of sales growth, the level of customer satisfaction, level of compliance with customer complaints, percentage of defective products, number of new products, level of job satisfaction, and employee productivity. The establishment of a performance measurement worksheet, so that the performance values of each performance indicator and total performance can be known in a certain period.Keywords: Performance, Measurement, Batik